Penerapan Metode SAW dalam Sistem Pendukung Keputusan Pemilihan Parfum pada Rancangan Aplikasi E-Commerce (Studi Kasus: Parfum Tridaya) - Al Godzali, Galva; Amartha, Alif Nur Fathlii; Athallah , Rafif Isdarufa; Saputra, Wisnu Ikhwansyah; Anshor, Abdul Halim (Jurnal Informasi, Sains dan Teknologi, 2024)
Changes in consumer shopping behavior encourage perfume stores to innovate in providing a better shopping experience. This study designs a website-based perfume recommendation system with the Simple Additive Weighting (SAW) method, which is designed to help consumers choose perfume based on relevant criteria, such as aroma, durability, price, packaging, and volume. The SAW method was chosen because of its ability to provide the best alternative ranking by adding up the weights of each criterion. The results showed that Platinum perfume had the highest preference value of 0.86466, making it the main recommendation for consumers. The implementation of this system is expected to significantly improve the shopping experience and perfume sales.